Corrosion protection in sulfate medium by self-assemb films adsorbed on AA 2024 T3 aluminum alloy surface - Viomar,Aline (2015)
In this study, the corrosion protection provided by films of self-assembled molecules on the AA 2024-T3 aluminum alloy has been evaluated by electrochemical and non electrochemical techniques. The film was obtained by immersion of this alloy samples in a solution of 90 mg L-1 alkane-diphosphonate at 50 °C for 5 minutes. Chromating conversion treatment with trivalent or hexavalent chromium was carried out by immersion of AA 2024-T3 alloy samples for 2 minutes in a 20% (v/v) solution of 650 Chromical TCP (SurTec) at 40 °C. Electrochemical characterization was performed by measurements of the open circuit potential (OCP), potentiodynamic polarization curves (PPC) and electrochemical impedance spectroscopy (EIS) in a solution of 0.5 mol L-1 sodium sulfate buffered with a solution of biphthalate potassium (0.1 mol L-1) and sodium hydroxide (0.1 mol L-1) as the electrolyte. SAM films obtained were analysed by infrared spectroscopy and SAM was found in surface. Surface observation by scanning electron microscopy (SEM) showed that the trivalent chromium layers ere deposited on metal surface. The results show that the surface treatment with self-assembled molecules provides protection against corrosion of the AA 2024-T3 aluminum alloy.